A rule based approach for implementation of bangla to english translation - Rahman, Md. Khalilur; Tarannum, Narzu (© 2012 IEEE, 2017)
This conference paper was presented in the International Conference on Advanced Computer Science Applications and Technologies, ACSAT 2012; Kuala Lumpur; Malaysia; 26 November 2012 through 28 November 2012 [© 2012 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ACSAT.2012.98